The Synthesis and Biological Evaluation of Mycobacterial p-Hydroxybenzoic Acid Derivatives (p-HBADs) - LAVELLE, EDWARD; SCANLAN, EOIN (My University, 2014)
Mycobacterium tuberculosis establishes chronic infection and causes disease through manipulation of the host's innate and adaptive immune response. The bacterial cell wall is highly complex and contains a rich variety of glycosylated compounds that are secreted during infection and have been proposed as immunomodulatory molecules. Amongst the most important of these are the p-hydroxybenzoic acid derivatives (p-HBADs). Here we report the synthesis of this important class of biomolecules and the first in vitro study of the immunomodulatory effects of these compounds in isolation from the host bacterium. The compounds do not have stimulatory properties but, in contrast, can inhibit the production of inflammatory cytokines, particularly interferon-? (IFN-?), by T-cells. This study offers a fundamental insight into the effect of these glycans on the immune response.
PUBLISHED
PMID: 24424275
Keywords: Tuberculosis; Immunology, Inflammation & Infection